The Epidemiology of Primary Biliary Cholangitis in European Countries: A Systematic Review and Meta-Analysis - Jakub Gazda; Sylvia Drazilova; Martin Janicko; Peter Jarcuska (Canadian Journal of Gastroenterology and Hepatology)
Background. Primary biliary cholangitis (PBC) is a chronic autoimmune cholestatic liver disease with wide ranges of reported incidence and prevalence. Aim. To map the incidence and prevalence of PBC in European countries from 2000 through 2020. Methods. Following PRISMA recommendations, we searched the Medline and Scopus databases for studies with information on either the incidence or prevalence of PBC. After data extraction, we used a random-effects model to estimate both the pooled annual incidence rate and pooled point-prevalence rate and performed subgroup analyses to identify components contributing to between-study heterogeneity. Results. We performed a qualitative and quantitative analysis of 18 studies. The pooled point-prevalence rate was 22.27 cases per 100,000 inhabitants (95% CI: 17.98–27.01), and the pooled annual incidence rate was 1.87 new cases per 100,000 inhabitants (95% CI: 1.46–2.34). In the subgroup analyses, we proved that a small part of the between-study heterogeneity is significantly associated with a history of being part of the Eastern Bloc.